Challenges and opportunities with drug repurposing: finding strategies to find alternative uses of therapeutics - Talevi, Alan (2019)
Drug repurposing(or repositioning) implies finding new therapeutic indications for existingdrugs (including approved, failed, discontinued and experimental drugs), andrepresents a substantial percentage of recent drug approvals, generating anestimated revenue of USD 250 billion per annum (25% of the total revenue).Accordingly, the drug discovery community is now actively engaged in organized,systematic drug repositioning.Here, we present a brief overview of the mainchallenges faced by repurposing projects, including legal and commercialbarriers, the need of tools to assimilate heterogeneous large-scale data, andthe fact that the universe of repurposing candidates is finite and expandsslowly, possibly requiring to progressively move repurposing efforts tounexplored areas of therapeutics.Opportunities within the field are alsobriefly presented, including newcollaborative models and the impact ofprecision medicine, ar also discussed.